TOURISM DEVELOPMENT WITH QUALITY TOURISM APPROACH IN ULOS HUTARAJA VILLAGE - Maleachi, Sandra; Juliana, Juliana; Sianipar, Rosianna; Sitorus, Nova Bernedeta (Jurnal Ilmiah Global Education, 2023)
This study aims to know the development of the tourism quality in Ulos Hutaraja Village. This study used qualitative research methods. Overall, the quality of tourism in Kampung Ulos Hutaraja is strongly influenced by several factors. First, tangible factors include adequate infrastructure and physical facilities, such as accommodation, transportation, tourist attractions, restaurants and shops that meet quality standards. Second, is the responsiveness factor, which includes the ability of tourism managers to provide services that are responsive to the needs and expectations of tourists. Third, the assurance or guarantee factor involves security, comfort, and trust in the tourism experience. Fourth is the reliability factor, which emphasizes consistency, timeliness, and service continuity. Fifth, the participant factor highlights the participation of local communities in tourism development, which can provide a more authentic experience and protect the environment. Sixth is the accessibility factor, which relates to adequate transportation and infrastructure access. In addition, cultural authenticity is essential in maintaining and promoting local culture as the main attraction for tourists, maintaining cultural integrity and avoiding excessive commercialization. Finally, cohesiveness or harmony is an essential indicator of maintaining a balance between tourism, the environment and local communitiy welfare through natural preservation, cultural preservation, tourism impact research, sustainable policies, fair social and economic benefits, and collaboration with related parties. By paying attention to these factors, Kampung Ulos Hutaraja can build quality, sustainable and beneficial tourism for all parties involved.